2021
DOI: 10.1161/atvbaha.120.315393
|View full text |Cite
|
Sign up to set email alerts
|

Hmox1 (Heme Oxygenase-1) Protects Against Ischemia-Mediated Injury via Stabilization of HIF-1α (Hypoxia-Inducible Factor-1α)

Abstract: Objective: Hmox1 (heme oxygenase-1) is a stress-induced enzyme that catalyzes the degradation of heme to carbon monoxide, iron, and biliverdin. Induction of Hmox1 and its products protect against cardiovascular disease, including ischemic injury. Hmox1 is also a downstream target of the transcription factor HIF-1α (hypoxia-inducible factor-1α), a key regulator of the body’s response to hypoxia. However, the mechanisms by which Hmox1 confers protection against ischemia-mediated injury remain to be f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 63 publications
4
47
0
Order By: Relevance
“…Furthermore, remifentanil preconditioning led to a remarkable increase in HIF-1 level the cardiac tissues. Notably, recent studies have revealed that elevated HIF-1 could protect the organs from I/R-induced damage through potentiating antioxidant activity and facilitating cell survival [37][38][39]. Besides, cell model experiments showed that remifentanil preconditioning significantly reversed the increase in intracellular ROS accumulation and apoptosis of H9c2 cardiomyocytes triggered by hypoxia/reoxygenation exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, remifentanil preconditioning led to a remarkable increase in HIF-1 level the cardiac tissues. Notably, recent studies have revealed that elevated HIF-1 could protect the organs from I/R-induced damage through potentiating antioxidant activity and facilitating cell survival [37][38][39]. Besides, cell model experiments showed that remifentanil preconditioning significantly reversed the increase in intracellular ROS accumulation and apoptosis of H9c2 cardiomyocytes triggered by hypoxia/reoxygenation exposure.…”
Section: Discussionmentioning
confidence: 98%
“…The precise mechanism remains to be determined, although action on KCa 2+ channels in the outflow pathway has been suggested ( Dong et al, 2007 ; Bucolo and Drago, 2011 ). Recent work in a model of hind limb ischemia suggests the stabilization of HIF-1α by hemeoxygenase 1 (Hmox1) is at least partially attributed to carbon monoxide, with carbon monoxide a by-product of the breakdown of heme by of Hmox1 ( Dunn et al, 2021 ). In addition, carbon monoxide regulates mitochondrial biogenesis and gene expression, suggesting multiple protective sites in glaucoma are possible ( Cherry and Piantadosi, 2015 ).…”
Section: Hypoxia Contributes To Inflammationmentioning
confidence: 99%
“…Of note, the endogenous neovascularization mediated by high blood pressure and shear stress was frequently lack of lumen, and it thus might not be effectively involved in the blood circulation in the ischemic tissues [ 22 ]. The sustained hypoxia was responsible for failure of muscle recovery, extensive tissue necrosis, and severe muscle mass loss [ 23 ]. As shown in Figures 1(e) and 1(f) , the ischemic hind limbs of the mice in the model group presented the phenotypes of muscle fiber degeneration, necrosis, inflammation, and calcification, which could be rescued by 30 and 90 mg/kg of Tan IIA.…”
Section: Resultsmentioning
confidence: 99%